PIWIL1 gene polymorphism and pediatric acute lymphoblastic leukemia relapse susceptibility among Chinese children: a five-center case–control study - Ding, Wenjiao; Wang, Dao; Cai, Mansi; Yan, Yaping; Liu, Shanshan; Liu, Xiaodan; Luo, Ailing; Deng, Decheng; Liu, Xiaoping; Jiang, Hua (Frontiers in Oncology, 2023)
Objective PIWIL1 polymorphisms’ role in pediatric acute lymphoblastic leukemia (ALL) relapse susceptibility remains undiscovered. Methods A case–control designed and multiple logistic regression model was performed to evaluate the overall risk of pediatric ALL and five single-nucleotide polymorphisms (SNPs) of PIWIL1 gene (rs35997018 C>T, rs1106042 A>G, rs7957349 C>G, rs10773771 C>T, and rs10848087 A>G) in 785 cases and 1,323 controls, which were genotyped by TaqMan assay. The odds ratio (OR) and its 95% confidence interval (CI) were used to estimate the relationship. Stratified analysis was used to investigate the correlation of rs1106042 and rs10773771 genotypes and pediatric ALL relapse susceptibility in terms of age, sex, number of white blood cells (WBC), immunophenotyping, gene fusion type, karyotype, primitive/naïve lymphocytes, and minimal residual disease (MRD) in bone marrow. Finally, the haplotype analysis was performed to appraise the relationship between inferred haplotypes of PIWIL1 and pediatric ALL risk. Results Among the five analyzed SNPs, rs1106042 A>G was related to increased ALL risk, and rs10773771 C>T was related to decreased ALL risk. Compared to the GG genotype, the rs1106042 GA/AA had a deleterious effect on children of age <120 months, who were female and male, had high or average number of WBC, pro-B ALL, pre-B ALL, T-ALL, low- and middle-risk ALL, E2A-PBX fusion gene, non-gene fusion, abnormal diploid, high hyperdiploid, hypodiploid, and normal diploid. Moreover, rs1106042 A>G harmfully affected primitive/naïve lymphocytes and MRD on days 15–19, day 33, and week 12. On the contrary, rs10773771 TC/CC exhibited a protective effect on ALL children with the TEL-AML fusion gene. Haplotype analysis demonstrated that haplotypes CAGT, TACC, TACT, and TAGT were significantly associated with increased pediatric ALL relapse susceptibility. Conclusion PIWIL1 rs1106042 A>G was related to increased ALL risk, and rs10773771 C>T was linked to decreased ALL risk in eastern Chinese children. Rs1106042 GA/AA may predict poor prognosis.